The impact of repeated rounds of mass drug administration with diethylcarbamazine plus albendazole on bancroftian filariasis in Papua New Guinea. - Gary J Weil; Will Kastens; Melinda Susapu; Sandra J Laney; Steven A Williams; Christopher L King; James W Kazura; Moses J Bockarie (Public Library of Science (PLoS), 2008)
This study employed various monitoring methods to assess the impact of repeated rounds of mass drug administration (MDA) on bancroftian filariasis in Papua New Guinea, which has the largest filariasis problem in the Pacific region.Residents of rural villages near Madang were studied prior to and one year after each of three rounds of MDA with diethylcarbamazine plus albendazole administered per World Health Organization (WHO) guidelines. The mean MDA compliance rate was 72.9%. Three rounds of MDA decreased microfilaremia rates (Mf, 1 ml night blood by filter) from 18.6% pre-MDA to 1.3% after the third MDA (a 94% decrease). Mf clearance rates in infected persons were 71%, 90.7%, and 98.1% after 1, 2, and 3 rounds of MDA. Rates of filarial antigenemia assessed by card test (a marker for adult worm infection) decreased from 47.5% to 17.1% (a 64% decrease) after 3 rounds of MDA. The filarial antibody rate (IgG(4) antibodies to Bm14, an indicator of filarial infection status and/or exposure to mosquito-borne infective larvae) decreased from 59.3% to 25.1% (a 54.6% decrease). Mf, antigen, and antibody rates decreased more rapidly in children <11 years of age (by 100%, 84.2%, and 76.8%, respectively) relative to older individuals, perhaps reflecting their lighter infections and shorter durations of exposure/infection prior to MDA. Incidence rates for microfilaremia, filarial antigenemia, and antifilarial antibodies also decreased significantly after MDA. Filarial DNA rates in Anopheles punctulatus mosquitoes that had recently taken a blood meal decreased from 15.1% to 1.0% (a 92.3% decrease).MDA had dramatic effects on all filariasis parameters in the study area and also reduced incidence rates. Follow-up studies will be needed to determine whether residual infection rates in residents of these villages are sufficient to support sustained transmission by the An. punctulatus vector. Lymphatic filariasis elimination should be feasible in Papua New Guinea if MDA can be effectively delivered to endemic populations.